If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x) + ln(x + -6) = ln(8x + -24) Multiply ln * x lnx + ln(x + -6) = ln(8x + -24) Reorder the terms: lnx + ln(-6 + x) = ln(8x + -24) lnx + (-6 * ln + x * ln) = ln(8x + -24) lnx + (-6ln + lnx) = ln(8x + -24) Reorder the terms: -6ln + lnx + lnx = ln(8x + -24) Combine like terms: lnx + lnx = 2lnx -6ln + 2lnx = ln(8x + -24) Reorder the terms: -6ln + 2lnx = ln(-24 + 8x) -6ln + 2lnx = (-24 * ln + 8x * ln) -6ln + 2lnx = (-24ln + 8lnx) Solving -6ln + 2lnx = -24ln + 8lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '24ln' to each side of the equation. -6ln + 24ln + 2lnx = -24ln + 24ln + 8lnx Combine like terms: -6ln + 24ln = 18ln 18ln + 2lnx = -24ln + 24ln + 8lnx Combine like terms: -24ln + 24ln = 0 18ln + 2lnx = 0 + 8lnx 18ln + 2lnx = 8lnx Add '-8lnx' to each side of the equation. 18ln + 2lnx + -8lnx = 8lnx + -8lnx Combine like terms: 2lnx + -8lnx = -6lnx 18ln + -6lnx = 8lnx + -8lnx Combine like terms: 8lnx + -8lnx = 0 18ln + -6lnx = 0 Factor out the Greatest Common Factor (GCF), '6ln'. 6ln(3 + -1x) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing l to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Add 'x' to each side of the equation. -1x + x = -3 + x Combine like terms: -1x + x = 0 0 = -3 + x Simplifying 0 = -3 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 15x^2+x=75 | | -105=-7(2k+1) | | (x+3)+2=0 | | 11x-2+6x+7=90 | | (3y+5)+(2x+1)=85 | | 28-42=154 | | 6x-48=66 | | .25(16+12x)=28 | | 180-x/2=2(90-x)-24 | | 4x+3y+2z=24 | | 8x-4=56 | | -5y+44=4(y+2) | | -5.1z=-11.53 | | 180-x/2=180-2x-24 | | y^3+0.4898=5.02*y^2 | | 3(y-7)=-2y+24 | | 2.25+.20x=7.65 | | 3(y-7)=2y+24 | | 2(m+6)+2(m-2)=24 | | 0.19w=0.722 | | 4x+3y+2z=20 | | 2x+7=q | | 3w-17=-4(w-8) | | 2.25+.20x=6.05 | | 7(2x+3)+5x= | | 3r^2-13r=-4 | | -5(w+5)=-8w-22 | | y^3+0.4898=5*y^2 | | http://opt-prod.s3.amazonaws.com/traject/files/item_attachments/relateds/000/184/832/original/Equation_1.PNG?1463559653 | | 3(6x+5)=2(5+9x) | | x^3+21x^2+108x=0 | | 5(4y-2)=52 |